Securing Multi-Cloud Environment: An Automated Data Deletion System with Integrated Intrusion Detection System Over Multi-Cloud Platforms - Singh, Jashanbir; Bhathal, Gurjit Singh (International Journal of Computer Sciences and Engineering, 2024)
The recent rapid growth of cloud service providers as more and more users and organizations are moving towards the multi-cloud systems, so that data can be accessed from any part of the world but it poses a humongous problem related to security and privacy of data. Cloud industry needs robust data security system. This research study investigates the feasibility, challenges, and potential impacts of implementing an automated data deletion system, integrated with the capabilities of intrusion detection, in a multi-cloud environment. Through qualitative methods, the aim to understand the experiences, perspectives, and insights of key stakeholders involved in the deployment and operation of such systems. Data collection methods include surveys of focused groups with cloud security experts, IT managers, compliance officers, and developers and an in-depth analysis of existing models and architectures, internal reports, whitepapers, policy documents, compliance guidelines, and security incident records. This research provides an insight and in-depth understanding of the requirements of the individual users and stakeholders of various organizations and improving the overall efficiency of multi-cloud environments by implementing the proposed Automated Data Deletion System with Intrusion Detection System.